Geschichtsbewusstsein und Zeitzeugnis. Nietzsches Genealogie als Anregung zum philosophischen Dialog mit Kindern - Marsal, Eva; Tobashi, Takara (ETHICS IN PROGRESS, 2014)
The paper confronts the reader with Nietzchean critical approach to history, truth, life, and education. Far away from progressive-euphoric ideologies of 19th, the authors consider the following questions: How children live historical occurences when being tought in classrooms (for example in Italy, Japan, etc.), how can we strengthen their ability for reflected relations to history as well as for interconnecting between past, present, and future life? Psychological, pedagogical, and philosophical considerations meet intercultural contexts.